Źródła stresu w pracy zawodowej menedżerów: The sources of stress among managers - Wróblewska, Violetta (Management and Administration Journal, 2021)
Stress is the active response of an organism to the challenges and threats that it faces. It appears as a result of a discrepancy between expectations and the ability to fulfill them. The purpose of the article was to determine the factors which cause stress among managers at their place of work. These factors can include shortage of time, necessity of making difficult decisions in a hurry, conflicting and ambiguous roles, the lack of balance between one’s work and private live, divergence between the values propagated by an organization and their actual implementation, excessive tasks, fear of losing the job, working under time pressure, high pace of work, necessity of working overtime, loss of control, excessive control, low salary, unsatisfying professional career, big responsibility for people and assets, working till late hours, fatigue which contributes to decline of an effective performance, the nature of interpersonal relations between a manager and his/her superior as well as a manager and an employee reporting to him/her.